Effects of maternity leave expansion on female labour demand and birth rates : a theoretical analysis - Lim, Gan Shu (2010)
This paper aims to investigate the effects of extended maternity leave on female labour demand and the overall birth rate. To address these issues, we develop two models based on the cost-benefit analysis and optimisation approach respectively. In essence, the models demonstrate several important insights. First, the effects of more maternity leave on female labour demand depend on the nature of a job, but are generally deleterious to female job applicants. Second, longer maternity leave does not necessarily incentivise women to have more children. To the extent that the models hold true, they imply that extended maternity leave, while an appealing policy option, can actually backfire. There is also a limit to how far birth rates can increase, if at all, in response to a longer period of paid maternity leave, especially in developed countries. This gives rise to the need for policies that influence such fundamentals as attitudes toward having children, rather than maternity leave alone. Given the crucial implications of both models, we recognise the importance of further empirical research in testing their predictive power.